Comparison of Disease Phenotypes and Clinical Characteristics Among South Asian and White Patients with Inflammatory Bowel Disease at a Tertiary Referral Center. Issue 12 (7th March 2020) - Bodiwala, Vimal; Marshall, Timothy; Das, Kiron M; Brant, Steven R; Seril, Darren N
Abstract: Background: The prevalence and clinical features of inflammatory bowel disease (IBD) vary among different racial and ethnic groups. The aim of this study was to compare the clinical and phenotypic features of Crohn's disease (CD) and ulcerative colitis (UC) in South Asian patients living in the United States with those of a white cohort. Methods: The demographic, clinical, and phenotypic characteristics of 73 South Asian patients (31 CD and 42 UC) who presented initially to our tertiary referral center from 2012 to 2016 and had subsequent follow-up were retrospectively compared with those of 408 consecutive white patients (245 CD and 163 UC). Results: South Asian IBD patients were significantly more likely to have UC (58.0% vs 40.0%; P = 0.005) than white patients. South Asians with CD were less likely to have a family history of IBD (9.7% vs 26.9%; P = 0.037) and required fewer CD-related surgeries (22.5% vs 46.1; P = 0.012). South Asians were also less likely to be active or former smokers in both the CD ( P = 0.004) and UC ( P = 0.020) groups. South Asians with UC had a higher incidence of Clostridium difficile infection compared with white patients (19.0% vs 8.6%; P = 0.050). Conclusions: A cohort of South Asian patients with IBD were more likely to have UC and had differing family and tobacco risk factors, requirements for surgery, and Clostridium difficile infection rates as compared with white patients.